2005
DOI: 10.1002/14651858.cd003235.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Emergency interventions for hyperkalaemia

Abstract: Analysis 23.1. Comparison 23 IV bicarbonate plus IV salbutamol versus IV insulin-glucose, Outcome 1 Serum potassium. Analysis 24.1. Comparison 24 IV insulin-glucose plus IV bicarbonate plus IV salbutamol versus IV insulin-glucose, Outcome 1 Serum potassium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
131
0
11

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 142 publications
(145 citation statements)
references
References 29 publications
3
131
0
11
Order By: Relevance
“…[1][2][3][4][5][6] Sodium polystyrene sulfonate (SPS) is a potassiumbinding resin commonly used to treat mild acute or chronic hyperkalemia by increasing the excretion of potassium in stool. 7 SPS is predominantly used for mild hyperkalemia (defined as serum potassium between 5 and 6 mmol/L), where the risk of complications is low.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6] Sodium polystyrene sulfonate (SPS) is a potassiumbinding resin commonly used to treat mild acute or chronic hyperkalemia by increasing the excretion of potassium in stool. 7 SPS is predominantly used for mild hyperkalemia (defined as serum potassium between 5 and 6 mmol/L), where the risk of complications is low.…”
Section: Introductionmentioning
confidence: 99%
“…A Cochrane review found no trial evidence of major outcome benefit for any emergency hyperkalaemia therapy with the best efficacy when medical (as opposed to dialysis) potassium lowering is required was for beta agonists and intravenous insulin-and-glucose. [7] The safety of neither therapy has been established specifically in the HF population. In view of their risks beta agonists are usually avoided in HF.…”
Section: Hyperkalaemiamentioning
confidence: 99%
“…These considerations support instituting acute therapy for patients with moderate-to-severe hyperkalemia according to the criteria specified above, 33 although minimal evidence from clinical trials is available on the acute treatment of hyperkalemia. 36 Some data suggest that ZS-9 37 and patiromer 38 may have an onset of action sufficient to allow the use of these agents in the acute setting. More data are needed to fully understand these findings and determine whether the observation of an early effect (1-4 hours with ZS-9) was because of shifting potassium (ie, because of postprandial insulin release in patients who were fasting before ZS-9 was administered or alkalization from the conversion of the sodium component of ZS-9 to bicarbonate), or to true potassium removal.…”
Section: Practical Clinical Management Of Hyperkalemia Acute Hyperkalmentioning
confidence: 99%